Characterization of Periwinkle Shell Powder as a Possible Replacement for Asbestos in the Production of Automotive Disc Brake Linings - Mawuli, Seckley Emmanuel; Anthony, Simons; Akintunde, Dahunsi Olurotimi (European Journal of Applied Sciences, 2025)
This study investigates the potential of Periwinkle Shell (PS) powder as a substitute for asbestos in friction lining materials, given the carcinogenic nature of asbestos. Periwinkle, a small univalve gastropod mollusk, specifically Tympanotonos fuscatus (commonly called the West African Mud Creeper), is explored for its suitability in industries like construction and brake pad manufacturing. However, there is limited research on the properties of periwinkle shell. To address this gap, the study characterizes the PS powder using a range of tests, including mechanical testing, X-ray Diffraction (XRD), X-ray Fluorescence (XRF), Differential Scanning Calorimetry-Thermogravimetric Analysis (DSC-TGA), and Scanning Electron Microscopy-Energy Dispersive Spectroscopy (SEM-EDS). The findings show that the density of PS powder (1.316 g/cm³ for untapped bulk density and 1.718 g/cm³ for dry bulk density) is lower than that of asbestos, which has a density of 2.22 g/cm³. Additionally, the chemical and mineralogical compositions of PS powder are similar to asbestos, both containing silica, calcite, anhydrite, and quartz, as indicated by the presence of SiO₂, CaO, MgO, and Al₂O₃. In terms of thermal stability, PS powder exhibits comparable properties to asbestos, with a peak degradation temperature of 745.88 °C and a total weight loss of 16 % for PS powder, versus 700 °C and 11 % weight loss for asbestos. These results suggest that PS powder could be a viable alternative to asbestos in automotive friction lining materials.